2020
DOI: 10.7150/jca.49554
|View full text |Cite
|
Sign up to set email alerts
|

Erzhu Jiedu decoction ameliorates liver precancerous lesions in a rat model of liver cancer

Abstract: Precancerous lesions are the intermediate stage in the development of liver cancer from cirrhosis. Early intervention measures can effectively prevent the occurrence of liver cancer and prolong the lives of patients, resulting in greater economic effects. Erzhu Jiedu decoction (EJD) is a semiempirical formula that is used in the treatment of cirrhosis and liver cancer according to the academic philosophy of “Preventive treatment of disease” and has achieved good curative effects in clinical practice. The purpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
(35 reference statements)
1
7
0
Order By: Relevance
“…This result suggests that CMFs had a positive effect on tumor marker, which was consistent with the finding of Cheng Y. (Cheng et al, 2020). Generally speaking, CMFs could prolong the survival rate, ameliorate the quality of life, diminish solid tumors, and lower tumor markers in PLC patients at the intermediate-advanced stage.…”
Section: Discussionsupporting
confidence: 87%
“…This result suggests that CMFs had a positive effect on tumor marker, which was consistent with the finding of Cheng Y. (Cheng et al, 2020). Generally speaking, CMFs could prolong the survival rate, ameliorate the quality of life, diminish solid tumors, and lower tumor markers in PLC patients at the intermediate-advanced stage.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, EZJDR effectively reduced the DEN-induced GST-Pi, AFP, CK19, c-Myc, and Ki67 protein expression in liver precancerous tissues. [23] EZJDR is a Chinese herbal medicine that has been prescribed for the treatment of chronic viral hepatitis B, liver cirrhosis and HCC for many years in clinical experience, we found that patients who took EZJDR had a good clinical effect. To confirm this phenomenon, we performed this clinical study.…”
Section: Discussionmentioning
confidence: 78%
“…More importantly, EZJDR could improve the general conditions (body weight, ALT, AST, and GGT) and reduced the number of precancerous lesions in the rat model which induced by diethylnitrosamine (DEN). Moreover, EZJDR effectively reduced the DEN-induced GST-Pi, AFP, CK19, c-Myc, and Ki67 protein expression in liver precancerous tissues [23] …”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations